K-State Turfgrass Research 2003 - Kansas State University. Agricultural Experiment Station; Cooperative Extension Service (Kansas Agricultural Experiment Station Research Reports, 2003)
Turfgrass Research 2003 contains results of projects done by K-State faculty and graduate students. Some of these results will be presented at the Kansas Turfgrass Field Day at the John C. Pair Horticultural Research Center in Wichita on August 7, 2003. Despite current budget restraints, the turfgrass teaching, research, and extension programs are strong. In addition to ongoing work in Manhattan and Wichita, turf research has been initiated at the new research center in Olathe and will be expanding in the coming years. Our strength is attributed, in part, to the support provided by members of the Kansas turfgrass industry.If you need information on selecting the best turfgrass varieties for our region, you'll find that information here. This publication also contains information about controlling tough weeds such as yellow nutsedge and spurge and diseases such as brown patch and dollar spot. Significant work was done in 2002 to identify irrigation requirements of grasses in our state and how turf managers can conserve water; you'll find that inside as well.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 911; Turfgrass; Diseases; Drought; Irrigration; Tall Fescue; Bluegrass; Ryegrass; Fescue; Zoysiagrass